2007
DOI: 10.1007/s10509-007-9341-y
|View full text |Cite
|
Sign up to set email alerts
|

Radio emission from AXP and XDINS

Abstract: The result of the search for, and the observations of radio emission from two groups of isolated neutron stars: AXP 1E 2259+586 and XDINS 1RXS J1308.6+212708 and 1RXS J214303.7+065419 are reported. The observations were carried out on two sensitive transit radio telescopes at a few frequencies in the range 42-112 MHz. The flux densities, mean pulse profiles, as well as, the estimation of the dispersion measures, distances and integrated radio luminosities of all objects are presented. Comparison with X-ray dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…We found that as soon as magnetar oscillations are taken into account, their death lines in the P − B diagram shift downward and the conditions necessary for the generation of radio emission in the magnetosphere are met. Present observations (Malofeev et al (2007), Malofeev et al (2010)) showing a close connection between the burst activity of magnetars and sporadic detection of the radio emission from some magnetars are naturally accounted for within our interpretation.…”
supporting
confidence: 81%
“…We found that as soon as magnetar oscillations are taken into account, their death lines in the P − B diagram shift downward and the conditions necessary for the generation of radio emission in the magnetosphere are met. Present observations (Malofeev et al (2007), Malofeev et al (2010)) showing a close connection between the burst activity of magnetars and sporadic detection of the radio emission from some magnetars are naturally accounted for within our interpretation.…”
supporting
confidence: 81%
“…Also, the non-detection of radio emission from X-ray dim isolated neutron stars (XDINSs) thus far (Kondratiev et al 2009), could be due to the beams of these long-period sources being quite narrow at high frequencies and there may be a better chance to detect them in radio at LOFAR frequencies. In fact, weak radio emission from two XDINSs, RX J1308.6+2127 and RX J2143.0+0654, was reported by Malofeev et al (2005Malofeev et al ( , 2007 at 111 MHz, hence it would be important to confirm this detection with LOFAR. This is also the case for the pulsars discovered in blind searches of Fermi gamma-ray photons, many of which do not exhibit detectable radio emission (Abdo et al 2009(Abdo et al , 2010b, as well as the remaining unidentified gamma-ray sources, which have characteristics of radio pulsars but which have not yet been detected in the radio (Abdo et al 2010a).…”
Section: New Populationsmentioning
confidence: 97%
“…X-ray pulsations (P = 3-12 s) have Based on observations collected at ESO, Paranal, under Programmes 66.D-0128(A), 078.D-0162(A). 1 The claimed low-frequency pulsed emission from two of them (Malofeev et al 2007) has not been confirmed yet.…”
Section: Introductionmentioning
confidence: 97%